Writing Assessment Strategies by Junior High School English Teacher - Yossy Kevin Parulian Pardede; Dwi Mutiara Tember Sari Silaban; Sara Okta Romindo Sibarani; Erikson Saragih (Linguistic, English Education and Art (LEEA) Journal, 2022)
Research intends to define assessment in writing, implement writing assessment, the evidence of this research is descriptive qualitative, by distributing questionnaires as research instruments in the form of google form. The result data were collected by utilizing the data from the essay test results. This study shows that writing assessments are in the form of planning, implementation, and assessment which are obstacles for teachers in learning. In this study, the teacher's strategies in assessing students' abilities in writing skills were found, namely; Constructive and Contextual methods; rubrics; Simple Text; Essays; Case Studies; Problem Based Learning. And the result of this study indicate that learning to write can improve vocabulary, pronounciation and spelling well. Keywords: assessment strategies, junior high school, writing assessment